Radical hysterectomy and vaginectomy with sigmoid vaginoplasty for stage I vaginal carcinoma. Issue 2 (16th May 2013) - Yin, Duo; Wang, Ning; Zhang, Shulan; Huo, Naichen; Xiao, Qian; Ling, Ouyang; Lu, Yanming; Wei, Heng
Abstract: Objective: To evaluate the therapeutic value of radical hysterectomy and vaginectomy with sigmoid vaginoplasty among patients with International Federation of Gynecology and Obstetrics stage I vaginal carcinoma. Methods: A retrospective study was conducted of 5 women (age range, 45–55 years) with stage I vaginal carcinoma who underwent surgery at Shengjing Hospital of China Medical University, Shenyang, China, between January 4, 2009, and December 30, 2011. All participants had lesions in the upper third of the vagina and wished to retain sexual function. Patients underwent radical hysterectomy and vaginectomy with pelvic lymphadenectomy, followed by sigmoid vaginoplasty for vaginal reconstruction. Results: The mean operative time was 248.0 ± 39.6 minutes and the mean intraoperative blood loss was 335.0 ± 76.6 mL. All patients recovered well after surgery and no delayed complications or recurrence were experienced during a mean follow‐up of 22.8 ± 9.98 months. None of the patients developed vaginal stenosis and all were satisfied with their postoperative sexuality. The mean Female Sexual Function Index was 28.0 ± 1.92. Conclusion: Radical hysterectomy and vaginectomy with sigmoid vaginoplasty was a reasonable option for patients with stage I vaginal carcinoma who wished to retain sexual function after surgery.